The librarian´s role and the construction of knowledge: articulation strategies with instructors - Malagon Ruiz, Rusby Yalile
The present article reflects the results taken during IV National Library System Conference in 2015, organised by the Management Library System Team from the National Instructors School `Rodolfo Martínez Tono´, where a didactic proposal was developed in order to build collectively proposals for the intervention in culture and information. The methodological perspective is framed under the action research; due to the results, it is conclusive that librarians express some concerns to invigorate their role and to involve instuctors in the knowledge construction, and that the knowledge they poses, product of a daily practice, must be recognised and invigorated through dialogue and participation channels.